ANALISIS PRAKTIK PINJAMAN ONLINE DENGAN SISTEM BUY NOW PAY LATER DITINJAU DARI HUKUM BISNIS SYARI’AH - Muhammad Widad; Trinah Asi (JURNAL ILMIAH NUSANTARA, 2024)
The presence of online lending platforms with the Buy Now Pay Later (BNPL) model has become an innovative convenience in the modern financial ecosystem. Despite the convenience of payment facilities, the practice of online lending through Buy Now Pay Later has raised significant issues in its implementation. This phenomenon shows that the Buy Now Pay Later facility presents risks, including the risk of customers experiencing difficulties in repayment.This research is normative juridical research. Normative juridical research is one approach in the legal field that focuses on the analysis of existing legal norms. In normative juridical research, this study finds the coherence of truth, which is whether legal rules are in accordance with legal norms and whether the norms in the form of orders or prohibitions are in line with legal principles, as well as whether a person's actions are in accordance with legal norms. In this study, the phenomenon of Buy Now Pay Later, which is a product of fintech innovation and also involves lending agreements, will be reviewed from the perspective of Sharia Business Law norms and studies.The results of the research show that the practice of online lending with the Buy Now Pay Later system can have complex implications in Sharia business law. Although this financial instrument provides convenient financial access for consumers, on the other hand, it can pose risks of riba (interest) and gharar (uncertainty) that are contrary to Sharia principles. Online financial service providers that impose high fees and interest are clearly against Islamic legal principles, particularly Sharia economic law, where justice and equality are considered principles that must be upheld. Riba clearly violates this principle as it generates unfair profit between the lender and the borrower.